Gut-Liver Axis Links Portal Hypertension to Acute-on-Chronic Liver Failure - Trebicka, Jonel (Visc Med, 2018)
Acute-on-chronic liver failure (ACLF) is considered a distinct syndrome in patients with liver disease, with systemic inflammation playing a central role. Portal hypertension (PHT) is also aggravated by inflammation and may subsequently impact the course of ACLF. PHT is more than just an increase in portal pressure in the portal venous system; it aggravates the course of liver disease and, thus, also facilitates the development of acute decompensation and ACLF. A critical mechanistic link between PHT and ACLF might be the gut-liver axis, which is discussed in this review.